O Atlântico enfermo e os agentes da saúde no período do tráfico ilegal - Kodama, Kaori (Afro-Ásia, 2020)
Resenha de: BARCIA, Manuel. The Yellow Demon of Fever: Fighting Disease in the Nineteenth-Century Transatlantic Slave Trade. New Heaven: Yale University Press, 2020. 269p.